2007
DOI: 10.1073/pnas.0607026104
|View full text |Cite
|
Sign up to set email alerts
|

Rapid induction of virus-neutralizing antibodies and viral clearance in a single-source outbreak of hepatitis C

Abstract: In contrast to a detailed understanding of antiviral cellular immune responses, the impact of neutralizing antibodies for the resolution of acute hepatitis C is poorly defined. The analysis of neutralizing responses has been hampered by the fact that patient cohorts as well as hepatitis C virus (HCV) strains are usually heterogeneous, and that clinical data from acute-phase and long-term follow-up after infection are not readily available. Using an infectious retroviral HCV pseudoparticle model system, we stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
491
3
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(519 citation statements)
references
References 43 publications
(66 reference statements)
20
491
3
5
Order By: Relevance
“…In contrast, approximately 30% of individuals who become infected with HCV spontaneously clear the infection (23), even though the viral diversity in HCV-infected individuals is comparable to or exceeds that of the diversity of HIV isolates in HIV-infected subjects (24)(25)(26)(27). Spontaneous clearance of HCV has been associated with effective innate and T cell responses, but we and others have shown that spontaneous clearance is associated with early appearance of broadly neutralizing antibodies against HCV in serum (28,29). mAbs from individuals with broadly neutralizing serum and clearance of HCV have not been isolated to date, so it is not known whether these mAbs have unique features relative to the mAbs previously isolated from individuals with persistent HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, approximately 30% of individuals who become infected with HCV spontaneously clear the infection (23), even though the viral diversity in HCV-infected individuals is comparable to or exceeds that of the diversity of HIV isolates in HIV-infected subjects (24)(25)(26)(27). Spontaneous clearance of HCV has been associated with effective innate and T cell responses, but we and others have shown that spontaneous clearance is associated with early appearance of broadly neutralizing antibodies against HCV in serum (28,29). mAbs from individuals with broadly neutralizing serum and clearance of HCV have not been isolated to date, so it is not known whether these mAbs have unique features relative to the mAbs previously isolated from individuals with persistent HCV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding of virus neutralization by antibodies is important for vaccine development, since prior studies have shown that antibodies that neutralize HCV play an important role in immune-mediated control of the virus, and that neutralizing antibody resistance mutations may reduce viral replicative fitness (Gottwein et al, 2009;Lavie et al, 2014;Osburn et al, 2014;Pestka et al, 2007). However, study of HCV neutralizing antibodies has been hindered by lack of standardized methods to measure virus entry and neutralization, and by inadequate genetic diversity in viral panels.…”
Section: Introductionmentioning
confidence: 99%
“…HCVpp have greatly advanced the understanding of HCV entry and neutralization by antibodies (Giang et al, 2012;Law et al, 2008;Morin et al, 2012;Osburn et al, 2014;Pestka et al, 2007). This model system has been used extensively in identifying HCV cell surface receptors required for viral entry (Bartosch et al, 2003;Cormier et al, 2004;McKeating et al, 2004;Zhang et al, 2004), and studies using HCVpp have established that neutralizing antibodies can drive evolution in vivo of HCV E1E2, leading to neutralization escape (Dowd et al, 2009;Pestka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…nAbs that primarily target the HCV envelope glycoproteins E1 and E2 have been identified during natural HCV infection (7)(8)(9)(10). However, more recent studies have highlighted a protective role for HCV nAbs during the acute phase of infection that are associated with recovery (11)(12)(13).…”
mentioning
confidence: 99%